2014
DOI: 10.1007/s00330-014-3154-5
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced spectral mammography in patients referred from the breast cancer screening programme

Abstract: • CESM is feasible in the workflow of referrals from routine breast screening. • CESM is superior to mammography, even in low disease prevalence populations. • CESM has an extremely high negative predictive value for breast cancer. • CESM is comparable to MRI in assessment of breast cancer extent. • CESM is comparable to histopathology in assessment of breast cancer extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
85
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 21 publications
3
85
1
3
Order By: Relevance
“…The domain "patient selection" and 'flow and timing' were the domains potentially contributing a high risk of bias, and particularly the 'patient selection' domain: only the study by Lobbes et al [7] was considered to be at relatively low risk of bias because the patients who underwent CESM were enrolled prospectively from a screening population. All the other studies were scored as at high risk of bias in the domain "patient selection" because CESM was performed on very selected populations.…”
Section: Quality Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…The domain "patient selection" and 'flow and timing' were the domains potentially contributing a high risk of bias, and particularly the 'patient selection' domain: only the study by Lobbes et al [7] was considered to be at relatively low risk of bias because the patients who underwent CESM were enrolled prospectively from a screening population. All the other studies were scored as at high risk of bias in the domain "patient selection" because CESM was performed on very selected populations.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…These methods are based on the biological principle of rapid formation of tumoral microvessels that render malignancy associated vessels more permeable to contrast agent than normal tissue, resulting in tumour enhancement [6]. Contrast-enhanced spectral mammography (CESM), a new imaging technique based on this principle, uses mammography in combination with iodine-based contrast agents to increase diagnostic capability through detection of areas of increased vascularization in the breast [7]. A review on contrast-enhanced mammography techniques found encouraging preliminary results with a mean sensitivity of 85.2% (range 62.0e96.0%) and a mean specificity of 66.1% (range 50.0e83.3%) [7e9].…”
mentioning
confidence: 99%
“…The depiction of breast cancers using contrast media is based on the biologic principle of the rapid formation of tumoral microvessels that render malignancyassociated vessels more permeable to contrast agent than normal tissue, resulting in tumor enhancement. 7 It has been proposed by Chang et al, that the use of a standard iodinated CT contrast agent and x-ray imaging might also give functional information with a preferential uptake in breast cancers. 8 An early study done among 26 subjects in 2003 by Lewin et al, of the University of Colorado utilizing dual-energy contrastenhanced mammography showed tumor enhancement in 13 of the subjects that had subsequent biopsy-proven invasive cancers.…”
Section: Contrast-enhanced Spectral Mammography (Cesm)mentioning
confidence: 99%
“…Systematic biases can also be observed depending on the choice of imaging modality: use of MRI has a tendency to lead to overestimates of tumor size (3,5), whereas underestimation of size is more common when mammography or ultrasound is used (4,5). Recently, dual-energy contrast-enhanced spectral mammography (CESM) has emerged as a potential new option for breast cancer staging by allowing for improvements in breast cancer tumor visualization (6) and may be equivalent to MRI for tumor size assessment (7,8). CESM, also commonly referred to as contrast-enhanced digital mammography, operates under the principle that iodinated contrast agents injected into the blood stream will have different uptake patterns between hypervascularized breast lesions and background breast parenchyma and that dual-energy subtraction imaging will allow for selective visualization of the distribution of the contrast agent in the breast with minimal anatomic background ''noise'' to obscure the lesion.…”
mentioning
confidence: 99%